Basic Training: A Primer on Military Life and Culture for Health Care Providers and Trainees - Matthew Goldenberg; Derrick A. Hamaoka; Patcho N. Santiago; James E. McCarroll (Association of American Medical Colleges, 2012)
Abstract Active and retired military members comprise about 10% of the nation's adult population. Since more than 65% of American physicians receive at least some of their professional training in Veterans Affairs hospitals, most physicians will provide care for service members, veterans, and/or their families at some point during their professional careers. This computer-based, highly generalizable, user-friendly, and self-guided tutorial is designed to enhance health care providers' and trainees' knowledge of military life and culture in order that they may be better able to provide culturally competent care to service members, veterans, and their families. Because this is a new resource, there are no data yet to illustrate its effectiveness, but we anticipate that it can become a highly utilized resource to assist health care providers and trainees gain a better understanding of the military lives of their patients.